Azimuthal decorrelations and multiple parton interactions in γ+2 jet and γ+3 jet events in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Anikeev, V. B.; et al. (American Physical Society (APS), 2011)
Samples of inclusive γ+2 jet and γ+3 jet events collected by the D0 experiment with an integrated luminosity of about 1fb-1 in pp̄ collisions at √s=1.96TeV are used to measure cross sections as a function of the angle in the plane transverse to the beam direction between the transverse momentum (pT) of the γ+leading jet system (jets are ordered in pT) and pT of the other jet for γ+2 jet, or pT sum of the two other jets for γ+3 jet events. The results are compared to different models of multiple parton interactions (MPI) in the pythia and sherpa Monte Carlo (MC) generators. The data indicate a contribution from events with double parton (DP) interactions and are well-described by predictions provided by the pythia MPI models with pT-ordered showers and by sherpa with the default MPI model. The γ+2 jet data are also used to determine the fraction of events with DP interactions as a function of the azimuthal angle and as a function of the second jet pT. © 2011 American Physical Society.